Mini Review: Recent progress in RT-LAMP enabled COVID-19 detection (2020)
The coronavirus disease 2019 (COVID-19) pandemic has infected millions of people around the globe. The outbreak caused by the novel coronavirus (SARS-CoV-2) poses a great health risk to the public. Therefore, rapid and accurate diagnosis of the virus plays a crucial role in treatment of the disease and saving lives. The current standard method for coronavirus detection is the Reverse Transcription Polymerase Chain Reaction (RT-PCR) method. However, laboratorybased RT-PCR test for SARS-COV-2 requires complex facilities and elaborate training of operators, thus suffering from limit testing capacity and delayed results. Consequently, isothermal PCR such as Loop-mediated isothermal amplification (LAMP) has been emerging as a great alternative to the RT-PCR method. LAMP possesses some fundamental advantages such as amplification at a constant temperature, no need of a thermal cycler, a faster test result, and potentially a larger diagnostic capacity, while maintaining similar sensitivity and specificity, thus making it more suitable than the RT-PCR for monitoring a pandemic. Starting with a brief introduction of the working principle of LAMP method, this review summarizes recent progress in LAMP-enabled SARS-CoV-2 viral RNA detection. Lastly, future research directions are discussed. This critical review will motivate biosensor community in furthering the present research, which may pave the road for rapid and large-scale screening of SARS-CoV-2.